South Africa's growth, employment and redistribution strategy in the context of structural adjustment programmes in the South - Lehloesa, Thembinkosi L (Rhodes University, Faculty of Humanities, Department of Political Studies, 2000)
This study is a contribution to the ongoing debate concerning the future of South Africa's macro-economic policy known as the Growth, Employment and Redistribution (GEAR) strategy. The study attempts to draw parallels between the GEAR macro-economic policy framework and structural adjustment programmes in the South. By making use of this comparison, the study argues that the outcome of the GEAR will be no different from structural adjustment programmes in that it will fail to reduce poverty and cause government to meet the basic needs of the people. These conclusions are drawn from the fact that the GEAR policy is premised on the faith that the market is capable of redistributing income and wealth, and providing people with their basic needs.
Keywords: Growth, Employment And Redistribution Programme (South Africa)|South Africa -- Economic policy|South Africa -- Politics and government -- 1989-1994